Pengabdian Mahasiswa Asistensi Mengajar Melalui Program Klub Riset Matematika Siswa Kelas X UPTD SMAN 1 Majene - Nursyam Anaguna; Wisapna Nur Aulia; Asma Jelita (LPPM-IAI Hidayatullah Batam, 2026)
The Community Service Program conducted by teaching assistance students through the Mathematics Research Club at UPTD SMAN 1 Majene aimed to enhance conceptual understanding, learning motivation, and basic research skills of tenth-grade students using contextual and investigative learning approaches. This program implemented the Participatory Action Research (PAR) model, consisting of identifying initial conditions, analyzing learning problems, designing the program, carrying out research club activities, and conducting reflection. Data were collected through observations, semi-structured interviews, and documentation during the two-month implementation period. The results indicate 72,2% students’ engagement during discussions, confidence in expressing ideas, ability to solve contextual problems, and skills in conducting simple research using research-based worksheets. In addition to improving students’ numeracy literacy, the program strengthened the pedagogical, communication, and leadership competencies of the participating university students. Therefore, the Mathematics Research Club program has proven effective as a mentoring strategy that can create more active, collaborative, and meaningful learning for high school students.